Transcatheter balloon dilatation of cor triatriatum dexter with percutaneous atrial septal defect closure. Issue 2 (February 2022) - Hasnie, Usman A.; Prejean, Shane P.; Ahmed, Asmaa N.; Ahmed, Mustafa I.; Law, Mark A.
Abstract: Cor triatriatum dexter is an extremely rare congenital heart defect and cause of hypoxia in adults. We describe a case of cor triatriatum dexter discovered incidentally due to an iatrogenic atrial septal defect. The cor triatriatum dexter resolved with balloon dilation - a novel technique to manage this rare clinical condition. <Learning objective: Management of cor triatriatum dexter, an exceptionally rare diagnosis, has often been thought to be surgical. However, percutaneous intervention may be considered in select clinical situations.>